Urgensi Pengaturan Keamanan Maritim Nasional di Indonesia - Dhiana Puspitawati; Kristiyanto Kristiyanto (Jurnal Media Hukum, 2017)
Located between two continents and two oceans, Indonesia is vulnerable to various transnational crimes. Hence, the concept of maritime security emerged. This paper focuses on three crucial matters, maritime delimitation, IUU Fishing as well as piracy and armed robbery at sea. This research aims to analyze the urgency of national maritime security legal framework in Indonesia. This research uses normative method with statute approach and comparative approach. It is submitted that although regional dan international cooperation is important to address maritime threats, national legal instrument is also necessary. Unfortunately, Indonesia still does not have comprehensive national legal instrument in place. Thus, it is argued that Indonesia should formulate specific policy and national legal frameworks in addressing maritime threats completed with certain measures for each threats as well as point out which institutions competent in handling each threats.